Global prevalence of constipation in older adults: a systematic review and meta-analysis - Salari, Nader; Ghasemianrad, Mohammadrasool; Ammari-Allahyari, Mojtaba; Rasoulpoor, Shabnam; Shohaimi, Shamarina; Mohammadi, Masoud (Springer, 2023)
Background and objective Constipation is one of the most common functional disorders of the gastrointestinal tract in older adults. To date, no systematic review or previous meta-analysis has estimated the global prevalence of constipation in older adults. The prevalence of this disorder has been reported differently in different studies; therefore, this study aims to systematically review the publications and to perform a meta-analysis of the prevalence of constipation in older adults.